Hilwa Collections - Jamari, Amira Aisyah; Awg Bakar, Dayang Azleena; Omar, Nur Afika; Sulaiman, Atiqah Atahirah; Arifin, Juada; Abd. Sanih, Siti Masturah (2014)
The name of our company is Hilwa Collection boutique. This company will be establish on March 2014 and will be operates fully on March 2014. The capital of the company is by loan from the bank. We are planning to do a business about selling of muslimah wear cloths which are in stylish, elegant, modern, and fashionables that is suits for the everyday muslimah wear and for special occasion. . We had chosen Centere Point, Kota Kinabalu as a place of our business to operate. All of collections are made by using the best of garment such as cotton, chiffon, silk organza, lace fabric, sequin fabric, satin fabric, nylon and also visccon that we get from our suppliers. But the specialty of our business are, mostly of the collections was designed by Hilwa's designer and the customer can ask for their own styles and fashion that they want based on the garments that they can choose in our boutique. Hilwa Collection was a company that wants to become the first world's leading of Muslimah Fashion Boutique based on Islamic concept that will excite the consumer of all backgrounds and spark their curiosity to learn more about Islam. That is our vision while the is to provides attire and muhibbah for muslim ladies. For our objective, we will produce the high quality of cottons that suitable for our country's hot and humid weather. We also want to attract new customers and maintain our loyal customers besides build a strong relationship between organization and public. Each person on the organization has their own responsibility to ensure their workers to maintain and concentrate on the task that given. The marketing manager and their staff always considered to the judgmental and the new strategy. Because of Hilwa Collection is a muslimah boutique which is based on Islamic concepts, so will try to insert the valuable lessons of Islamic. It such as consists of honesty during the business running. As a conclusion, according from our discussion, we have learnt how to handle the company, how to make the decision even though it is a risk taking, how to planning the new strategy, how to manage the business or company, how to plays our roles responsibilities, how to communicate with the people, how to set the supervision, and how to administrative company based on the Islamic perspective.